Awareness and Understanding about Plagiarism among Higher Education Teachers in India - Singh, Gaurav (JOURNAL OF INDIAN EDUCATION, 2019)
Plagiarism is one of the most debatable topics among academicians these days. People are debating about its ethical viz-a-viz legal consequences. Many incidents of plagiarism have been reported in the recent past among teachers in higher education institutions. Media reports on these cases of plagiarism have developed anxiety and tension among Indian academicians. In this backdrop, the researcher has tried to study the awareness and understanding of plagiarism among higher education teachers in India. A mixed item self-reporting tool was administered on 232 teachers teaching in various affiliated colleges or university departments. Data was collected through both offline and online mode. Analysis of the data reflects that teachers have a basic understanding of only a few common types of plagiarism but not all. Teachers are in support to avoid plagiarism, but many of them are still not aware of a proper plagiarism detection mechanism. The study suggests that along with training and awareness programmes, plagiarism and its consequences should be a part of the research curriculum. The comprehensive guidelines are also required to promote academic honesty among teachers in colleges as well as in universities.